2017
DOI: 10.1002/2016jf003972
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Channel Head Bifurcation by Overland Flow

Abstract: Channel head bifurcation is a key factor for generating complexity of channel networks. Here we investigate incipient channel head bifurcation using linear stability analysis. Channel heads are simplified as circular hollows, toward which surface sheet flow accelerates in the radial direction. Sinusoidal perturbations in the angular direction with different angular wave numbers k are imposed on the bed, and their growth rates truenormalΩ~ are computed. Because the channel head radius trueR~c is extending ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In relation to transport‐limited erosion (e.g., Howard, ), the results of Smith and Bretherton () show that a channel‐cutting instability relating to nonlinearity in the transport of sediment underlies the process of channelization, with the boundary between stable and unstable flows forming an emergent CSB. An analogous instability for the case of detachment‐limited erosion (e.g., Howard, ) is described by Izumi and Parker (, ) and Pornprommin et al (), although the results of their stability analyses have been questioned (e.g., Smith, ). The analyses of Loewenherz () and Loewenherz‐Lawrence () indicate the necessity of stabilizing mechanisms that are capable of controlling the channel‐cutting instability and that lead to well‐defined channel networks.…”
Section: Introductionmentioning
confidence: 65%
“…In relation to transport‐limited erosion (e.g., Howard, ), the results of Smith and Bretherton () show that a channel‐cutting instability relating to nonlinearity in the transport of sediment underlies the process of channelization, with the boundary between stable and unstable flows forming an emergent CSB. An analogous instability for the case of detachment‐limited erosion (e.g., Howard, ) is described by Izumi and Parker (, ) and Pornprommin et al (), although the results of their stability analyses have been questioned (e.g., Smith, ). The analyses of Loewenherz () and Loewenherz‐Lawrence () indicate the necessity of stabilizing mechanisms that are capable of controlling the channel‐cutting instability and that lead to well‐defined channel networks.…”
Section: Introductionmentioning
confidence: 65%
“…To investigate the threshold condition, we adopted the recent linear stability analysis [3]. We calculated the threshold channel head radius for channelization (Rth) and compare it with the experimental average radius (R avg ) for every 1 second interval.…”
Section: Analysis Of Channel Head Evolutionmentioning
confidence: 99%
“…Thus, both studies showed that channel head bifurcation should be initiated by hydrophysical mechanisms (processes due to water forces such as erosion), not as a consequence of random topology. Pornprommin et al [3] performed a linear stability analysis using the flow equations in the polar coordination system to investigate incipient channel head bifurcation. Circular holes were assumed to be channel heads, toward which radial overland flow accelerates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations